Correlates of bird collisions with buildings across three North American countries. Issue 2 (22nd August 2020) - Elmore, Jared A.; Hager, Stephen B.; Cosentino, Bradley J.; O'Connell, Timothy J.; Riding, Corey S.; Anderson, Michelle L.; Bakermans, Marja H.; Boves, Than J.; Brandes, David; Butler, Eric M.; Butler, Michael W.; Cagle, Nicolette L.; et al.
Abstract: Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management. Abstract : Article Impact Statement : Species and life history predict bird collisions with buildings, and risk correlates vary by species. Abstract : Correlaciones de las Colisiones de Aves contra Edificios en Tres Países de América del Norte Resumen: Las colisiones contra los edificios causan hasta mil millones de fatalidades de aves al año en los Estados Unidos y en Canadá. Sin embargo, los esfuerzos por reducir estas colisiones se beneficiarían con estudios realizados a grandes escalas espaciales en varios sitios de estudio con métodos estandarizados y considerando las variaciones relacionadas a la historia de vida y a la especie y las correlaciones de las colisiones. Abordamos estas necesidades de investigación por medio de una recolección coordinada de datos sobre las colisiones de aves contra edificios en los Estados Unidos (35), Canadá (3) y México (2). Recolectamos todos los cadáveres y los identificamos hasta especie. Después de retirar los registros de cadáveres no identificados, las especies sin estimaciones poblacionales a nivel distribución y las especies con distribuciones traslapadas en menos de diez sitios, nos quedamos con 269 cadáveres de 64 especies para el análisis. Estimamos la vulnerabilidad a colisiones para 40 especies con ≥2 fatalidades con base en la abundancia poblacional para América del Norte, el traslape de su distribución entre los sitios de estudio y el esfuerzo de muestreo. De las diez especies que identificamos como las más vulnerables a las colisiones, algunas han sido identificadas previamente ( Setophaga caerulescens ), y otras aparecieron por primera vez ( Sitta carolinensis ), posiblemente debido a que usamos una estrategia de muestreo más estandarizada que en los estudios previos. El tamaño del edificio y el área del vidrio estuvieron asociados positivamente con el número de colisiones para cinco de ocho especies con suficientes observaciones para ser analizadas independientemente. La vegetación alrededor de los edificios influyó sobre las colisiones solamente para una de esas ocho especies Catharus ustulatus ). Las historias de vida pronosticaron las colisiones; el número de colisiones fue mayor para las especies migratorias, insectívoras y aquellas que habitan en las zonas boscosas. Nuestros resultados proporcionan una nueva perspectiva hacia las especies más vulnerables a las colisiones contra edificios, lo que las pone en una necesidad potencialmente mayor de atención conservacionista para reducir estas colisiones y de estudio de las variaciones relacionadas con la especie y la historia de vida y las correlaciones de las colisiones contra edificios, información que puede ayudar a refinar el manejo de colisiones. 摘要: 在美国和加拿大, 每年有多达10亿只鸟类死于撞击建筑物。在大空间尺度上跨多个研究地点、采用标准化方法, 并考虑鸟类物种及生活史变异和其它撞击相关因素的研究, 将有助于减少鸟类与建筑物的碰撞。本研究通过整理收集美国、加拿大和墨西哥多个位点 (数量分别为 35 个、3 个和 2 个) 鸟类撞击建筑物的数据来满足以上的研究需求。我们首先收集了所有鸟类尸体并进行物种鉴定。在排除掉不能辨认的尸体、缺少分布范围内种群估计数据的物种、分布区与少于 10 个位点有重叠的物种后, 我们保留了 64 个物种的 269 个死亡事件进行分析。我们根据鸟类的北美种群数量、分布区与研究位点的重叠情况和抽样工作量, 估计了死亡个体≥2 只的 40 种鸟类的撞击脆弱性。本研究确定了最易发生撞击的 10 个物种, 其中包括已经被以往研究提及的物种 (如黑喉蓝林莺 [ Setophaga caerulescens ]), 也有首次报道的物种 (如白胸鳾 [ Sitta carolinensis ]), 这可能是因为我们使用了比以往研究更注重标准化的抽样方法。在有足够观察数据以支持独立分析的 8 个物种中, 有 5 个物种的撞击次数与建筑大小和玻璃面积呈正相关;只有1个物种 (斯氏夜鸫 [ Catharus ustulatus ]) 的撞击受到建筑物周围植被的影响。生活史也可以预测撞击情况:迁徙鸟类、食虫鸟类和林栖鸟类的撞击次数最多。我们的研究结果为最易发生建筑物撞击伤害的鸟类物种提供了新的见解, 这些物种可能最需要保护以减少撞击, 本研究还深入探究了鸟类物种及生活史变异和其它撞击相关因素, 这些信息有助于改进鸟类撞击管理。【翻译: 胡怡思; 审校: 聂永刚】